Chemical constituents of Mussaenda erythrophylla Schumach. & Thonn. (Rubiaceae) and their chemophenetic significance. (October 2021) - Bouzeko, Inest Larissa T.; Dongmo, Faustine Léonie M.; Ndontsa, Blanche Laure; Ngansop, Cyrille Armel N.; Keumoe, Rodrigue; Bitchagno, Gabin Thierry M.; Jouda, Jean Bosco; Mbouangouere, Roukayatou; Tchegnitegni, Billy Toussie; Boyom, Fabrice Fekam; Sewald, Norbert; Lenta, Bruno Ndjakou; et al.
Abstract: The chemical investigation of the CH2 Cl2 /MeOH (1:1) extract from the aerial part of Mussaenda erythrophylla Schumach. & Thonn. (Rubiaceae) resulted in the isolation of sixteen known compounds (1 –16 ) distributed in coumarins, flavonoid glucosides, quinic acid derivatives, triterpenoids, monoglycerid, steroids, tetraterpenoid and polyol. The structures of the compounds were determined by spectrometric and spectroscopic analysis including MS and NMR data followed by their comparison with reported ones in the literature. The chemophenetic significance of the isolated compounds was discussed. The crude extract and some of the isolated compounds were assessed in vitro for their antileishmanial, cytotoxic and antiplasmodial activities. The crude extract of M. erythrophylla showed moderate antileishmanial activity (IC50 = 61.6 μg/mL) while the hexane soluble fraction showed good antileishmanial activity (IC50 = 31.06 μg/mL) compared to the reference drug amphotericin B (IC50 = 0.11 μM). Compounds 11 and 9 also exhibited potent antileishmanial activity (IC50 = 53.7–52.0 μM). The crude extract as well as the ethyl acetate soluble fraction also exhibited good antiplasmodial activity (IC50 = 7.43 ± 0.00 μg/mL and 14.49 ± 2.96 μg/mL respectively), while compounds 11, 15 and 16 showed weak activity with IC50 > 20 μM compared to the reference drug artemisinin (IC50 = 0.014 ± 0.001 μM). Graphical abstract: Image 1 Highlights: Sixteen compounds isolated from aerial of Mussaenda erythrophylla . The chemophenetic significance of isolates were studied. Structures were cleared by extensive NMR and MS techniques. Isolates showed moderate to significant cytotoxicity towards the parasites. Compounds were low to moderate active against the parasites.